Penyuluhan Untuk Meningkatkan Kunjungan Ibu Hamil, Pemeriksaan Kesehatan, dan Pemberian Tablet Fe Di Wilayah Kerja Puskesmas Matiti Tahun 2023 - Sihite, Helprida; Simamora, Debora Natalia (Jurnal Masyarakat Indonesia (Jumas), 2023)
Increasing visits by pregnant women for health checks is very important in supporting the health of the mother and fetus, as well as preventing complications during pregnancy and childbirth. This article examines the effectiveness of health education as a method to increase awareness and frequency of examination visits for pregnant women. Through a structured educational approach, health education can increase mothers' knowledge about the benefits of routine check-ups, pregnancy risk factors, and preventive measures. The results showed a significant increase in examination visits after the education intervention, indicating the importance of health education to support optimal antenatal care.